2023
DOI: 10.3934/microbiol.2023006
|View full text |Cite
|
Sign up to set email alerts
|

Study of the antibacterial effects of the starch-based zinc oxide nanoparticles on methicillin resistance <i>Staphylococcus aureus</i> isolates from different clinical specimens of patients from Basrah, Iraq

Abstract: <abstract> <p>This study aimed to assess the efficacy of starch-based zinc oxide nanoparticles (ZnO-NPs) against methicillin-resistant <italic>Staphylococcus aureus</italic> (MRSA) isolates from clinical specimens in Basrah, Iraq. In this cross-sectional study, 61 MRSA were collected from different clinical specimens of patients in Basrah city, Iraq. MRSA isolates were identified using standard microbiology tests, cefoxitin disc diffusion and oxacillin salt agar. ZnO-NPs were synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…102,103 Bioresorbable matrix of ZnONPs consists of collagen and 1% orange essential oil, but due to its high intrinsic toxicity at higher doses, its use is limited in wound therapy. 104 105 Copper nanoparticles (CuNPs) show good membrane penetrability and display antibacterial properties due to their ability to disrupt cell walls and bacterial membrane. 106 Released Cu 2+ ion and H 2 O 2 cause cytoplasm degradation, ultimately causing cell apoptosis.…”
Section: Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…102,103 Bioresorbable matrix of ZnONPs consists of collagen and 1% orange essential oil, but due to its high intrinsic toxicity at higher doses, its use is limited in wound therapy. 104 105 Copper nanoparticles (CuNPs) show good membrane penetrability and display antibacterial properties due to their ability to disrupt cell walls and bacterial membrane. 106 Released Cu 2+ ion and H 2 O 2 cause cytoplasm degradation, ultimately causing cell apoptosis.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…It inhibits the expression of superoxide‐dismutase and glutathione peroxidase gene and can potentiate carcinogenic transformation. Core‐shell nanocomposites are prepared by combining two metal ions (AuNPs from plant Hibiscus sabdariffa and zinc oxide), effective against resistant Staphylococcus haemolyticus and S. aureus through the release of ROS 105 …”
Section: Nanotechnology In Wound Therapymentioning
confidence: 99%
“…Complex metallic nanoparticles have a potential to be used as a bactericidal agent due to their physical, chemical, and biological properties (Balcucho et al, 2023; F. Pan, Giovannini, et al, 2022; Shi et al, 2023; Vasile et al, 2020). Indeed, nanoparticles such as gold (Shanwaz & Shyam, 2023; Zhan et al, 2022), silver (Esfahani et al, 2023; Hassan Afandy et al, 2023; Macovei et al, 2023), zinc oxide (Al‐Mosawi et al, 2023; Mousa et al, 2023; Xu et al, 2023), iron oxide (Shahriary et al, 2018), copper oxide (Bilal et al, 2022), titanium oxide (Abdolmajid et al, 2019), and gallium nanoparticles (Kircheva & Dudev, 2020; L. Li, Chang, et al, 2021; Pajor et al, 2020) have shown potential as antibacterial agents.…”
Section: Complex Metal Nanoparticles As Treatmentsmentioning
confidence: 99%